2008
DOI: 10.1539/joh.l7105
|View full text |Cite
|
Sign up to set email alerts
|

Different Mechanisms of DEHP‐induced Hepatocellular Adenoma Tumorigenesis in Wild‐type and Pparα‐null Mice

Abstract: Department of Preventive Medicine, ShinshuUniversity Graduate School of Medicine-Di (2-ethylhexyl) phthalate (DEHP) exposure is thought to lead to hepatocellular hypertrophy and hyperplasia in rodents mediated via peroxisome proliferator-activated receptor alpha (PPARα). A recent study revealed that long-term exposure to relatively low-dose DEHP (0.05%) caused liver tumors including hepatocellular carcinomas, hepatocellular adenomas, and chologiocellular carcinomas at a higher incidence in Pparα-null mice (25.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 35 publications
0
54
0
Order By: Relevance
“…It has been reported that PPs such as clofibrate, one of the fibrate drugs, and Wy-14,643, a widely used PP-representative compound, increase the number of peroxisomes, up-regulate peroxisomal beta-oxidation, and cause hepatocellular hypertrophy and hyperplasia when administered to rats and mice (Takashima et al 2008). In addition, Takashima et al (2008) added that PPARα-dependent alterations in cell cycle regulatory proteins are likely to contribute to the hepatocarcinogenicity of PPs. In the present study, all of the FF-treated mice exhibited centrilobular hypertrophy and vacuolar degeneration in hepatocytes, and some animals of this group had altered foci.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PPs such as clofibrate, one of the fibrate drugs, and Wy-14,643, a widely used PP-representative compound, increase the number of peroxisomes, up-regulate peroxisomal beta-oxidation, and cause hepatocellular hypertrophy and hyperplasia when administered to rats and mice (Takashima et al 2008). In addition, Takashima et al (2008) added that PPARα-dependent alterations in cell cycle regulatory proteins are likely to contribute to the hepatocarcinogenicity of PPs. In the present study, all of the FF-treated mice exhibited centrilobular hypertrophy and vacuolar degeneration in hepatocytes, and some animals of this group had altered foci.…”
Section: Discussionmentioning
confidence: 99%
“…Takashima et al [188] reported that that long-term exposure to a relatively low dose of DEHP (0.05%) caused liver tumors including hepatocellular carcinomas, hepatocellular adenomas, and chologiocellular carcinomas at a higher incidence in PPARa-null mice (25.8%) than wild type mice (10.0%). In contrast to Toyosawa et al [190], fewer tissues were examined for gene expression changes by Takashima et al [188].…”
Section: Tumor Phenotype and Alterations In Oncogenes And Suppressor mentioning
confidence: 99%
“…Data from animal and human studies suggest that EDCs may play a role in the development of cancer (Takashima et al 2008), the reported decline in human sperm count (Mocarelli et al 2008), temporal increases in the frequency of developmental abnormalities of the male reproductive tract (Sharpe & Skakkebaek 2008) and the trend towards precocious puberty in human females (Schoeters et al 2008).…”
Section: Introductionmentioning
confidence: 99%